SAFETY AND EFFECTIVENESS OF PIDOTIMOD IN ACUTE AND CHRONIC BRONCHITIS - A.V. Karaulov (Вопросы современной педиатрии, 2010)
One of effective and safe immunomodulators for prophylaxis and treatment of frequently ailing children is pidotimod (Imunorix). Efficacy of the drug in pediatric practice was studied in more than 3200 patients with acute and recurrent respiratory infections. The article shows reasonability of pidotimod administration in children with acute and chronic bronchitis. This fact was confirmed with doubleblinded placebo-controlled studies. Treatment with pidotimod results in decreased terms of recovery of chronic bronchitis exacerbation, shortening of exacerbation. Realization of stable effect is related to recovery of key functions of inborn and adaptive immunity, it begins in 15 days after intake of the drug in therapeutic dose. Prophylactic doses of pidotimod should be used during next 30–60 days.Key words: children, bronchitis, pidotimod, immunity, treatment.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(6):139-143)